2022
DOI: 10.1101/2022.04.21.489022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike variants differ in their allosteric response to linoleic acid

Abstract: The SARS-CoV-2 spike protein contains a fatty acid binding site, also found in some other coronaviruses (e.g. SARS-CoV), which binds linoleic acid and is functionally important. When occupied by linoleic acid, it reduces infectivity, by ‘locking’ the spike in a less infectious conformation. Here, we use dynamical-nonequilibrium molecular dynamics (D-NEMD) simulations to compare the response of spike variants to linoleic acid removal. These simulations show that the fatty acid site is coupled to functional regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 75 publications
(124 reference statements)
1
18
0
Order By: Relevance
“…D-NEMD simulations are emerging as a useful tool to probe signal propagation and allosteric effects, 38 e.g., they have identified a general mechanism of signal propagation in nicotinic acetylcholine receptors; 39,40 communication pathways between allosteric and active sites in clinically relevant β-lactamases; 30 and modulation of SARS-CoV-2 spike protein behaviour by pH 41 and ligand occupancy in the fatty acid binding site. [42][43][44] Notably in this context, the pathways identified in the β-lactamases contain positions that differ between enzymes with different spectrums of antibiotic breakdown activity. 30 In the D-NEMD approach, the system is sampled first by equilibrium molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…D-NEMD simulations are emerging as a useful tool to probe signal propagation and allosteric effects, 38 e.g., they have identified a general mechanism of signal propagation in nicotinic acetylcholine receptors; 39,40 communication pathways between allosteric and active sites in clinically relevant β-lactamases; 30 and modulation of SARS-CoV-2 spike protein behaviour by pH 41 and ligand occupancy in the fatty acid binding site. [42][43][44] Notably in this context, the pathways identified in the β-lactamases contain positions that differ between enzymes with different spectrums of antibiotic breakdown activity. 30 In the D-NEMD approach, the system is sampled first by equilibrium molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmon resonance experiments and cryo-EM structures show that the FA site is 3 conserved in the spike proteins of highly pathogenic β-coronaviruses, such as SARS-CoV, MERS-CoV, SARS-CoV-2, but not in the spikes of common, mild disease-causing β-coronaviruses (24). Simulations using the dynamical-nonequilibrium molecular dynamics (D-NEMD) approach showed that the FA site allosterically modulates the behaviour of functional motifs in both the ancestral (also known as wild type, 'early 2020', or original) spike and in several variants (25)(26)(27). These D-NEMD simulations showed that the FA site is allosterically connected to the RBM, N-terminal domain (NTD), furin cleavage site, and the region sourrounding the fusion peptide (FP) (25)(26)(27).…”
Section: Main Textmentioning
confidence: 99%
“…Here, we use D-NEMD simulations (38,39) to characterise the response to LA removal of the fully glycosylated SARS-CoV-2 ancestral spike to investigate allosteric modulation by the FA site and the effects of glycans on allosteric behaviour. D-NEMD simulations (38,39) have proved to be an effective approach to investigate responses of receptors (40)(41)(42), identify allosteric effects (25)(26)(27)(43)(44)(45)(46) and study effects of pH changes (47) in biomolecular systems, including SARS-CoV-2 targets (25-27, 45, 47). LA complex model was built using the cryo-EM structure 7JJI as a reference (23).…”
Section: Main Textmentioning
confidence: 99%
“…All glycosylation sites in the Original spike sequence as described by Zhao et al, (21) are retained in these variants. These equilibrium simulation data also provide the basis for dynamical non-equilibrium molecular dynamics simulations to map the allosteric pathways arising from the ligand annihilation from the fatty acid binding site in our accompanying paper (22).…”
Section: Introductionmentioning
confidence: 96%